ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUASAN MAHASISWA DI UNIVERSITAS MUHAMMADIYAH MAKASSAR - Rizal, Samsul (Jurnal Ekonomi Balance, 2011)
This study aims to analyze the influence of tuition fees, administrative services, learning quality as well as facilities and infrastructure of lectures towards student satisfaction at Muhammadiyah University of Makassar and analyze the most dominant factors affecting student satisfaction at Muhammadiyah University of Makassar. Data collection using questionnaires with the number of respondents as many as 300 people. Data analysis using factor analysis and multiple regression analysis. The result concluded that (1) Together variable of tuition, administration service, learning quality, as well as facilities and infrastructure of lecturing have positive and significant influence while partially variable of tuition fee, administration service and learning quality have positive and significant effect to student satisfaction in Muhammadiyah University of Makassar, but the variable facilities and lecture infrastructure influence is not significant. (2) Tuition variable is the most dominant variable affecting student satisfaction at Muhammadiyah University of Makassar.